2019
DOI: 10.1186/s12889-019-6598-3
|View full text |Cite
|
Sign up to set email alerts
|

“Workplace Physical Activity Program” (WOPAP) study protocol: a four-arm randomized controlled trial on preventing burnout and promoting vigor

Abstract: BackgroundWOPAP is a theoretically-grounded workplace physical activity intervention that aims to reduce work-related burnout and to improve vigor at work and other work-related outcomes. Using a randomized controlled trial, we investigate whether a 10-week program including two Nordic walking sessions per week is effective in improving employee well-being at work, in comparison with another attractive leisure activity (Theatre condition) or a waiting list control condition. The design of the study makes it po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 100 publications
0
7
1
3
Order By: Relevance
“…For example, for workers who perceive high levels of stress at work, doing a high weekly PA has a counterproductive role, reducing their levels of vigor at work. Despite Ginoux et al 51 found that PA, as a personal resource, improved the levels of vigor; and spending time doing PA had a positive effect on daily recovery 28 and more energy in workers 52 , the results of the present study showed that this resource may not always have such positive effects. According to Fodor et al 38 , a different association between stress and PA depending on the type of PA can take place.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, for workers who perceive high levels of stress at work, doing a high weekly PA has a counterproductive role, reducing their levels of vigor at work. Despite Ginoux et al 51 found that PA, as a personal resource, improved the levels of vigor; and spending time doing PA had a positive effect on daily recovery 28 and more energy in workers 52 , the results of the present study showed that this resource may not always have such positive effects. According to Fodor et al 38 , a different association between stress and PA depending on the type of PA can take place.…”
Section: Discussioncontrasting
confidence: 99%
“…With regard to work-related outcomes, over the last decades several mechanisms have been suggested to explain how regular PA participation affects employees' psychological functioning (Naczenski, de Vries, van Hooff, & Kompier, 2017). However, the underlying mechanisms of this association have not been fully elucidated yet (Ginoux, Isoard-gautheur, & Sarrazin, 2019). A combination of physical, social, and physiological mechanisms may offer preliminary support to understand this proposed association.…”
Section: Physical Activity and Work-related Outcomesmentioning
confidence: 99%
“…Finally, the use of a quasi-experimental design does not allow concluding to a causal relationship between the completion of the PA programme and changes in affective well-being across one month. As recently pointed out, the difficulty in randomly allocating participants in organizational settings is a limitation that should be overcome (Ginoux, Isoard-Gautheur, & Sarrazin, 2019).…”
Section: Discussionmentioning
confidence: 99%